PENGARUH TEMPERATUR PEMANASAN DAN WAKTU HOLDING SERAT DAUN NANAS TERHADAP KEKUATAN IMPACT KOMPOSIT EPOXY DENGAN METODE VACUUM INFUSION - Mohamad Irkham Mamungkas; Nur Subeki; M. Ulul Albab (ROTOR, 2021)
Technological developments, especially in the material sector, have led to new discoveries, one of which is the composite type material. Composites have been widely used in the automotive industry, both for exterior and interior. This is what encourages research on composites to continue to be developed. This study aims to determine the effect of heating temperature and heating time on pineapple leaf fibers on the impact strength using the vacuum infusion method. The temperature variations given are 70 °C, 80 °C, and 90 °C. While the variation of drying time is 1 hour, 2 hours, and 3 hours. Composite material manufacturing refers to ASTM D5942-96 standard. The results of this study indicate that the highest impact value occurs in specimens with a heating temperature variation of 80 ° C with a heating time of 3 hours, which is 0.075 Joules / mm². While the lowest impact strength occurs in specimens with a heating temperature of 70 ° C with a heating time of 2 hours, which is 0.01943 Joules / mm².